SAT0209 Mri evaluation of chondral lesions in knee osteoarthritis: arthroscopic correlation. (1st June 2001) - Acebes, C; Robledo, A; Granizo, J; Herrero-Beaumont, G
Abstract : Background: Arthroscopic exam evaluation (chondroscopy) of the articular cartilage is considered a relevant instrument of OA outcome for research purposes. Nevertheless availablity of other accurate but non-invasive methods for chondral evaluation in OA, such us MRI, should be desireble. Objectives: To evaluate the capacity of MRI to score chondropathy in knee OA compared with chondroscopy. Methods: 24 consecutive patients diagnosed of knee OA were referred for knee hyaline cartilage MR imaging of medial chondile and tibial plateau with a fat-suppressed spoiled gradient-echo sequences (SPGR) before chondroscopy. MRI and chondroscopic cartilage lesions evaluated by two methods were registered in an scale diagram and total score chondropathy was calculated using a software programme (Autocad). Correlation was determined by Sperman´s test for both evaluation (p < 0, 05). Results: High and significant intraobserver correlation was observed for evaluation of medial chondile and tibial plateau by chondroscopy r = 0, 806 and r = 0, 721 and by MRI r = 0, 805 and r = 0, 680 respectively. Correlation coefficient between chondroscopic and MRI score for chondile and tibia was r = 0, 781 and r = 0, 531 respectively. Conclusion: Fat-suppressed SPGR imaging seems to be a relevant tool for evaluation of cartilage lesions in OA of the knee showing a high correlation between both procedures. Both chondroscopy and MRI have a lower correlation for the detection of chondral lesions in tibial plateau than in femoral chondile. Supp. by a grant of Health Research Funding (98/626).